The impact of foreign ownership restrictions on inward FDI and economic growth: a case for BRICS countries - Hotane, Tsholofelo (My University, 2020)
This study sets out to investigate the impact of foreign ownership restrictions on the inflow of Foreign Direct Investments (inflow of FDI). The study further examines how the inflow of FDI subsequently affects the growth of host economies. The study employs panel data analysis over the period of twenty-one years (1997 – 2018), providing empirical evidence in BRICS economies. The findings reveal that ownership restrictions have a negative impact on the inflow of FDI, while FDI positively impacts economic growth. The results primarily provide guidance to the policy makers in the BRICS economies who are responsible for providing a conducive environment for investments.
A research submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Inflow of foreign direct investments (FDI inflows); BRICS; Emerging markets; Institutional factor; Ownership restrictions; Restrictiveness index; SDG-8: Decent work and economic growth